ANALISIS MANAJEMEN RISIKO OPERASIONAL BERDASARKAN PENDEKATAN ENTERPRISE RISK MANAGEMENT (ERM) PADA LKP TATIK MODES KABUPATEN TRENGGALEK - Faradillah Sandy, Mutiara Ike; Kurdi, Moh. (Journal MISSY (Management and Business Strategy), 2024)
Operations are one of the important things in the company, if the operation in good then the company will be good and vice versa. Company operations will also face risks, therefore the company must have risk management, one of which is ERM. This research uses descriptive qualitative methods with data collection techniques in the from of journals, publications, and interview with LKP Tatik Modes in Trenggalek Regency. The approach used in this research is Enterprise risk management (ERM), which can be applied with the steps of indentifying risk conducting assessments, and controlling risk. Through the application of ERM, companies can identify risks and classify them as low, medium, or high. The pupose of this study is to identify risks that may occur in the company and create a risk matrix to determine the most critical risks that should be prioritized for control. The results showed that operational risks at LKP Tatik Modes include occupational safety risks such as sewing machines that are difficult to control by novice participants, scrorched or perforated clothes when ironed by novice participants, and potential fires. Financial risks include fluctuating income as it depends on the number of participants who register. Environmental risks include potential flooding and power outages. Technological risks include social media being hacked. Human resource risks include theft of important data and damage to equipment.